P824 Accuracy of cervical cancer screening using a self-collected vial for HPV DNA testing among adult women in sub-saharan africa. (14th July 2019) - Nodjikouambaye, Zita Aleyo; Sadjoli, Damtheou; Sydney Mboumba Bouassa, Ralph; Péré, Hélène; Veyer, David; Adawaye, Chatté; Matta, Mathieu; Robin, Leman; Tonen-Wolyec, Serge; Tcheguena, Moll Mahamat; Moussa, Ali Mahamat; Koyalta, Donato; et al.
Abstract : Background: Cervical cancer is caused by HR-HPV infection. Self-collection of genital specimens and HPV DNA testing are methods increasing screening rates. The GYNAUTO-CHAD study compared the acceptability and HPV DNA diagnostic accuracy of clinician-collected endocervical sample with swab (as reference collection) and genital self-collection method with veil (V-Veil-Up Gyn Collection Device, V-Veil-Up Pharma Ltd., Nicosia, Cyprus) in adult women living in N'Djamena, Chad. Methods: Five of the 10 districts of N'Djamena were randomly selected for inclusion. Peer educators contacted women to participate to the survey by coming to the clinic for women's sexual health ' La Renaissance Plus '. A clinician performed pelvic examination and endocervical sampling using swab. Genital secretions were also obtained by self-collection using veil. Both clinician- and self-collected specimens were tested for HR-HPV DNA using Anyplex™ II HPV28 genotyping test (Seegene, Seoul, South Korea). Acceptability and accuracy of both collection methods were assessed. Results: 253 women (mean, 35.0 years) were prospectively enrolled. HPV prevalence was 22.9%, including 68.9% of HR-HPV (total HR-HPV prevalence: 15.8%), with unusual HR-HPV genotypes distribution and preponderance (70%) of HR-HPV targeted by Gardasil-9 ® vaccine. Veil-based genital self-collection showed high acceptability (96%), feasibility and satisfaction. Self-collection by veil was non-inferior to clinician-based collection for HR-HPV DNA testing, with 'good' agreement between both methods, high sensitivity (95.0%; 95%CI: 88.3–100.0%) and specificity (88.2%; 95%CI: 83.9–92.6%). Remarkably, the rates of HPV DNA and HR-HPV DNA positivity were significantly higher (1.67- and 1.57- fold, respectively) when using veil-based collection than clinician-collection. Conclusion: These observations highlight the unsuspected high burden of cervical oncogenic HR-HPV infection in Chadian women. Self-collection of genital secretions using the V-Veil-Up Gyn Collection Device constitutes a simple, highly acceptable and powerful tool to collect genital secretions for further molecular testing and screening of oncogenic HR-HPV that could be easily implemented in the national cervical cancer prevention program in Chad. Disclosure: No significant relationships.